Randomized Blind Controlled Study of the Incidence of Seminal Antispern Antibodies in Male with Primary Infertility in Kirkuk Governorate - Marbeen, Marah; Bra, Dhaher H.; Ghalib2, Ayla Kh. (Sulaimani Journal for Pure and Applied Sciences, 2007)
This is a randomized blind controlled prospective study included 123 males with primary infertility referred from private clinics from May 2004 to May 2005. ELISA was used to detect the antisperm antibodies in the seminal fluid of infertile males (60 patients with normal seminal fluid analysis and 63 patients with abnormal seminal fluid analysis). It was found that there was no significant difference in the incidence of antisperm antibodies between infertile males with normal seminal fluid analysis (10%) and those with abnormal seminal fluid analysis (%15.8) p>0.05, but most of infertile males with abnormal seminal fluid analysis (8 out of 10) their antibody titre was within high level (100-115) U/ml, while 5 out of 6 infertile patients with normal seminal fluid analysis, their antibody titre was with low level (60-75) years in both groups (infertile patients with normal seminal fluid analysis and abnormal seminal fluid analysis) and most affected infertile males were those with duration of infertility of 6-10 years. There was significant association (p<0.05) between smoking habit and abnormal seminal fluid analysis, while there was no significant difference between smoker and non smoker infertile males in the incidence of antisperm antibody (p>0.05).